2018
DOI: 10.1080/13603116.2018.1470686
|View full text |Cite
|
Sign up to set email alerts
|

Heads of alternative provision: committed to realising young peoples’ potential in an unregulated market

Abstract: Heads of alternative provision: committed to realising young peoples' potential in an unregulated marketAlternative provision caters for pupils who are marginalised and excluded from mainstream schooling. In England it is generally conceptualised in policy terms as providing education to support behavioural improvements (pupils are directed off site to improve behaviour). There is very limited research on the experiences of those who work in alternative provision settings. That which does exist tends to report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…But where AP resists easy categorisation by form, it provides some level of unity in terms of function: in the best APs, there is a sense of belonging and connectedness beyond that found in the mainstream (Jalali and Morgan 2018); the emphasis on relationships between children and staff and a flexibility of structure (Malcolm 2018); there is a tailored curriculum according to the interests and needs of the children (Mills and McGregor 2016); care is prioritised to create a safe space (O'Gorman, Salmon, and Murphy 2016). There is also some level of international uniformity for the sector found within the characteristics of the children that it serves with an over-representation of children from poorer backgrounds (Malcolm 2018;Skiba and Knesting 2002), children from black, Latino and mixed race backgrounds (Christle, Nelson, and Jolivette 2004;Smith 2009;Malcolm 2015) and children with special educational needs and disabilities (Trotman, Enow, and Tucker 2019;Brown 2007). Finally, there is the nature of the home contexts of children in AP: trauma, domestic and sexual abuse, teenage parenthood, neglect, family conflict, criminality, all featuring consistently in the international literature.…”
Section: Family Engagement In Alternative Provisionmentioning
confidence: 99%
“…But where AP resists easy categorisation by form, it provides some level of unity in terms of function: in the best APs, there is a sense of belonging and connectedness beyond that found in the mainstream (Jalali and Morgan 2018); the emphasis on relationships between children and staff and a flexibility of structure (Malcolm 2018); there is a tailored curriculum according to the interests and needs of the children (Mills and McGregor 2016); care is prioritised to create a safe space (O'Gorman, Salmon, and Murphy 2016). There is also some level of international uniformity for the sector found within the characteristics of the children that it serves with an over-representation of children from poorer backgrounds (Malcolm 2018;Skiba and Knesting 2002), children from black, Latino and mixed race backgrounds (Christle, Nelson, and Jolivette 2004;Smith 2009;Malcolm 2015) and children with special educational needs and disabilities (Trotman, Enow, and Tucker 2019;Brown 2007). Finally, there is the nature of the home contexts of children in AP: trauma, domestic and sexual abuse, teenage parenthood, neglect, family conflict, criminality, all featuring consistently in the international literature.…”
Section: Family Engagement In Alternative Provisionmentioning
confidence: 99%
“…(p. 11) For Sliwka (2008), the defining factors of AP are its emphasis on innovation in pedagogy and curriculum-a definitional lens that focuses on the child rather than the organisational type-innovation that is 'gaining popularity among parents, to create more holistic approaches to education and focus on student potential for growth ' (Sliwka & Yee, 2015, p. 175). This focus on the child is a common theme across the literature: Jalali and Morgan (2018) highlight the sense of belonging and connectedness not experienced in mainstream schools; Malcolm (2018) discusses the emphasis on relationships between staff and children, the flexibility of structure and curriculum; McCluskey et al (2015) evidence how AP settings actively listen to parents' views on working with their children; McGregor and Mills (2012) argue that the Australian 66 D. Page schools in their study focused on changing teaching and learning rather than changing the children, as does Quinn and Poirier (2006) in the USA; Mills and McGregor (2016) detail how the curriculum was tailored to the interests and goals of students; O'Gorman et al (2016) emphasise the prioritisation of care that creates the setting as a 'safe space'.…”
Section: Understanding Alternative Provision: An International Perspementioning
confidence: 99%
“…However, while there is consistency internationally on the child-centredness, innovation and flexibility of APs, defining the sector by its characteristics is problematic for three reasons: it underplays the impact (or absence) of government policy on AP and its concomitant determination of organisational forms. In the UK context, for example, Malcolm (2018) follows the government definition provided by Taylor (2012) as 'an organisation where pupils engage in timetabled, educational activities away from school and school staff'. Here, the complexity of AP is a result of policy: just as mainstream schools are designated as local authority, independent academies or free schools, APs follow the same diversity, including pupil referral units under council control, free schools, special schools and academies within a multi-academy trust (MAT).…”
Section: Understanding Alternative Provision: An International Perspementioning
confidence: 99%
See 1 more Smart Citation
“…These pupils are the result, the wasted lives, of the neo-liberal, marketised English schooling system (Mills, Renshaw and Zipin 2013). However, those working in AP see hope in these young lives and work to support them through their education (Garner 1996;Grundy and Blandford 1999;Farouk 2014;Malcolm 2018a). The research reported below sought to explore the experiences of those who had attended AP and the impact they perceive it to have had on their opportunities and experiences in life since then.…”
Section: Introductionmentioning
confidence: 99%